Association of Polycystic Ovary Syndrome Phenotypes With Adverse Pregnancy Outcomes After In-Vitro Fertilization/Intracytoplasmic Sperm Injection - Wang, Qiumin; Wang, Honghong; Li, Ping; Li, Xiufang; Wang, Ze; Yan, Lei; Shi, Yuhua (Frontiers in Endocrinology, 2022)
Abstract Objective: This study aims to evaluate the association between polycystic ovary syndrome (PCOS) phenotypes and adverse perinatal outcomes, that is based on comparing the characteristics, ovarian response and assisted reproductive outcomes in patients with various PCOS phenotypes after In vitro fertilization (IVF)/ Intracytoplasmic Sperm Injection (ICSI). Methods: This study retrospectively analyzed the clinical data of 6732 patients who underwent the first cycle of IVF/ ICSI treatment in our outpatient department from January 2017 to July 2018. Propensity score matching (PSM) was used in PCOS and non-PCOS groups to balance the influence of intergroup confounding factors. After the PSM procedure, 1186 patients were included in the two groups, respectively. And the PCOS patients were further divided into four PCOS phenotype groups based on Rotterdam criteria. Results: Patients with various PCOS phenotypes had similar rates of biochemical pregnancy, clinical pregnancy, and live birth (all P values＞0.05). The overall incidence of adverse pregnancy outcomes (including ectopic pregnancy, miscarriage, preterm birth) in PCOS phenotypes A and D groups were significantly higher than in the control group (44% & 46.4% vs. 28.7%, P=0.027). The rates of hypertensive disorder of pregnancy (HDP) were significantly higher in PCOS phenotypes A and C groups than in the control group (9.3% & 12.5% vs. 3.1%, P= 0.037). After adjustment for potential confounders, the differences of adverse pregnancy outcomes persisted (P=0.025). Conclusions: The overall incidence of adverse pregnancy outcomes in women with PCOS phenotypes A and D are higher than that in women with non-PCOS.